(untitled) (CHORNOMORSKI BOTANICAL JOURNAL, 2016)
We present the results of research macrophites algae Western Gulf of Dzharylgach Black Sea. The variety of algae species is represented by three divisions: Chlorophyta, Rhodophyta, Phaeophyta. In the investigated waters dominated by representatives of the division of Rhodophyta, which make up 47 % of the total number of found species of algae. Second place belongs Chlorophyta – 12 species (38 %). Among the representatives of Phaeophyta was discovered 5 species (15 %). When comparing the data with previous studies revealed changes in qualitative structure. Compiled taxonomic structure of algae Western Gulf of Dzharylgach Black Sea by family who dominated the algal flora in the study, the dominant species and species that have the highest frequency of occurrence.